2016
DOI: 10.1002/jbm.a.35678
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized titanium dioxide resulted in the activation of TGF‐β/Smads/p38MAPK pathway in renal inflammation and fibration of mice

Abstract: Titanium dioxide nanoparticles (TiO2 NPs) have been demonstrated to damage the kidneys. However, whether chronic nephritis leads to renal fibration or the fibrosis is associated with the activation of TGF-β/Smads/p38MAPK pathway caused by TiO2 NPs exposure is not well understood. Forty male mice were separately exposed to 0, 2.5, 5, or 10 mg/kg body weight TiO2 NPs for 6 months. Renal biochemical functions and levels of TGF-β/Smads/p38MAPK pathway-related markers and extracellular matrix (ECM) expression in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Smads mediate the signal transduction from TGF-β1. Smad3 is well known as a key regulator of fibrosis in many organ systems, and this is supported by the findings that mice lacking Smad3 are protected against fibrosis in multiple disease models (32)(33)(34). MAPK signaling is able to regulate fibrosis either independently or through cross-talk with Smad pathways (36)(37)(38).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Smads mediate the signal transduction from TGF-β1. Smad3 is well known as a key regulator of fibrosis in many organ systems, and this is supported by the findings that mice lacking Smad3 are protected against fibrosis in multiple disease models (32)(33)(34). MAPK signaling is able to regulate fibrosis either independently or through cross-talk with Smad pathways (36)(37)(38).…”
Section: Discussionmentioning
confidence: 87%
“…5C and D). considered to be the classical mechanism for fibrosis in physiological change induced by TGF-β1 (32). To confirm the fibrosis effect in MCs induced by TGF-β1, the level of Smad3 was detected and it was identified that TGF-β1 effectively enhanced the phosphorylation level of Smad3 in both MC genotypes.…”
Section: Expression Of Ep4 Protein Is Decreased Following Infection Wmentioning
confidence: 98%
See 2 more Smart Citations
“…The TGF-β1 signaling pathway is the most active. TGF-β is a multifunctional polypeptide growth factor that regulates cell proliferation, differentiation and apoptosis by complex receptor signaling pathways in the cell surface (19). TGF-β inhibits proliferation of glomerular epithelial cells and endothelial cells; however, it has a dual role on MCs: It stimulates proliferation at a low concentration, and inhibits proliferation at a high concentration (20).…”
Section: Discussionmentioning
confidence: 99%